A Case of Severe Leptospirosis with Pancytopaenia - Bee, P.C.; Chow, S.K.; Tan, L.H. (Malaysian Medical Association, 2003)
Pancytopaenia is a rare clinical presentation of severe leptospirosis. We would like to report a case of severe leptospirosis that progressed to pancytopaenia despite initial penicillin therapy. The patient needed a second course of antibiotic with doxycycline to improve his persistent symptoms and cytopaenia. Persistent pancytopaenia in severe leptospirosis and its management were reviewed.